Penolakan Penetapan Tersangka Korupsi Kepala Basarnas Oleh Komisi Pemberantasan Korupsi - Sopian, Ade (MATAKAO Corruption Law Review, 2024)
Introduction: The Corruption Eradication Commission has named the Head of Basarnas, who is also a member of the Indonesian National Army, as a suspect in the case of procurement of debris victim detection devices for the 2021-2023 Fiscal Year. The determination of the suspect received rejection from the TNI on the grounds that the Head of Basarnas was still an active officer of the Indonesian National Army. Purposes of the Research: This study aims to find out how the review of criminal law on the rejection of the Indonesian National Army over the designation of the head of Basarnas as a suspect in corruption crimes. Methods of the Research: the method used in this writing is normative legal research. What is meant by normative legal research is a research process to research and examine law as norms, rules of legal principles, legal principles, legal doctrines, legal theories and other literature. Results of the Research: of the research show that with the refusal to determine the suspect carried out by the Indonesian National Army and taking over the process of handling corruption through the Military Court, the Corruption Eradication Commission loses its authority, so that the actions of the Indonesian National Army Military Police Center can be subject to criminal liability. The Connectivity Court can be a middle ground in law enforcement of corruption cases involving military and civilian members, so as not to eliminate the authority of one of the agencies. In response to this situation, it is necessary to reform material laws related to the status of military members who commit general crimes and the handling of corruption crimes through the connectivity mechanism.